Relationship between overweight, obesity and physical fitness of thirteen and fourteen-year-old Macedonian adolescent - Vujica Živkovic; Lidija Todorovska; Lence A. Veličkovska; Serjoža Gontarev; Ruždija Kalac (University of Banja Luka, Faculty of physical education and sport, 2014)
The aim of this research is to determine the fitness level of the Macedonian adolescents, including adolescents from both sexes with different variables of their body mass indexes (BMI). The research has been carried out on 1835 adolescents and students from 19 elementary schools throughout Central and Eastern Macedonia. The sample (average age being 13.43 ± .5) was split into two sub-samples in relation to their gender, 933 being male and 902 being female respondents. Five anthropometric measurements (IBP methodology) were used in the research, in which the body fitness was analyzed using the following parameters: estimating motor skills applying seven tests of the Eurofit fitness testing battery; body composition by applying the BIA; aerobic capacity by applying a 3-minute step test. The results have been statistically analyzed using the SPSS, v. 20.0 for Windows (variance analysis, Spearman's correlation analysis and the test). The percentage of the overweight children, classified according to the BMI is equal to 31% of the Macedonian adolescents of the same age. Both male and female respondents with a high or an increased BMI have lower muscle mass percentage and show poor test results in the evaluation of the body strength, explosive power, speed, agility and coordination, as well as a low aerobic capacity.